Rain oscillations in Amparo de São Francisco, Sergipe - Brazil tooth 20 - 20 years (Research, Society and Development, 2022)
The objective is to analyze the average rainfall distributions between 1963 and 2019, observing the possible behaviors of their variability, taking into account the evaluation of the years in order to identify the years with the largest and smallest rainfall fluctuations, which occur every 20 years and providing information in relation to the thermal spatial and temporal variation in Amparo de São Francisco, Sergipe. Monthly and annual rainfall data were acquired from the Northeast Development Superintendence (SUDENE) and from the Sergipe Agricultural Development Company (EMDAGRO) between 1963 and 2019. For this purpose, the rainfall data was separated every 20 years, or that is, the periods 1963-1982 were characterized; 1983-2001 and 2002-2019, their historical arithmetic means and their respective graphs were computed.